UJI EFEKTIVITAS ANTIOKSIDAN KRIM EKSTRAK ETANOL BIJI PEPAYA (Carica papaya L.) TERHADAP DPPH (1,1-diphenyl-2-picrylhydrazil) - ., Orlen Veronica Solichin (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Seeds of papaya (Carica papaya L.) is a part of plant that potentially as a naturalantioxidant. This study aims to determine the IC50 values, physical and chemical propertiesand antioxidant activity of ethanol extract of papaya seeds cream compared with positivecontrol. This research was conducted by the DPPH (1,1-diphenyl-2-picrilhydrazil) methodby spectrophotometric at Î» max 516.0 nm. Cream consists of 5 formulas with variousconcentrations of the extract FI 0.8%, 1.6% F II, F III 2.4%, 3.2% F IV and FV 4%. Theresults showed that the ethanol extract all the cream papaya seeds have greater antioxidantactivity than the positive control. F II had the highest activity at 94.228% with IC50 valueof 867.68 Âµg/ml. PH and particle size of all cream is good, but the cream F III, F IV and FV had creaming. F II scent most favored, while the color, consistency and sensation of theskin which is most preferred to the F I. Based on the phytochemical screening, ethanolextract of papaya seeds contain phenols, flavonoids, alkaloids and vitamin C. Keywords: Ethanol Extract of Papaya Seed, Antioxidants, DPPH.